Novel approaches that promote lung endothelial and epithelial repair and anti pro inflammatory cytokines could be a future promising agent in the management of ARDS - Montaser Alrjoob; Alaa Alkhatib; Rana Padappayil; Husam Bader; Doantrang Du; Chandler Patton (Clinical Immunology Communications, 2023)
The acute respiratory distress syndrome (ARDS) is a common cause of respiratory failure in critically ill patients and is defined by the acute onset of noncardiogenic pulmonary edema, hypoxemia, and the need for mechanical ventilation. ARDS occurs most often in the setting of pneumonia, sepsis, aspiration of gastric contents or severe trauma, and is present in ∼10% of all intensive care unit patients worldwide. Pathologic specimens from patients with ARDS most frequently reveal diffuse alveolar damage, and laboratory studies have demonstrated both alveolar epithelial and lung endothelial injury, resulting in accumulation of protein-rich inflammatory edema fluid in the alveolar space. The current therapeutic regimen is comprised of supportive measures such as lung protective ventilation, restrictive fluid management, paralyzing drugs, and prone positioning. Although vast improvements have been made in ARDS-treatment during the last five decades, mortality among patients with severe ARDS remains at an unacceptable rate of 45%.This article reviews the evolution of the currently used definition, established pathophysiological mechanism, highlights the current best clinical practice to treat ARDS, gives a brief outlook on cutting edge trends in ARDS research and closes with an expert opinion on the subject. The ongoing digital revolution will help to individualize ARDS-treatment and will therefore presumably improve survival and quality of life.